ON THE SAFETY OF ANTIBACTERIAL DRUGS USED IN PEDIATRICS - A. R. Titova; E. Y. Pasternak; I. L. Asetskaya; S. K. Zyryanov; V. A. Polivanov; R. N. Alyautdin; B. K. Romanov (Безопасность и риск фармакотерапии, 2018)
The safety of application of different groups of antibacterial drugs in pediatrics among children is discussed in this article. The analysis was made of spontaneous reports in the national database for 2012, containing information about serious adverse reactions (AR) on antibiotics in the pediatric population. In addition to evaluating the overall structure of serious AR and their distribution to system organ classes, the role of different pharmaco-therapeutic groups of antibacterial drugs in the development of adverse effects of pharmacotherapy was analyzed. Particular attention was drawn to «off-label» prescriptions; their frequency and structures. It was shown that antibiotics are common cause of serious AR among children, and their use as «off-label» prescribed drugs is an additional risk factor for such reactions.